Influence of Glass Additions on Illitic Clay Ceramics - Shishkin, Andrei; Baronins, Janis; Mironovs, Viktors; Lukáč, František; Štubňa, Igor; Ozolins, Jurijs (Materials, 2020)
A mixture of an illitic clay and waste glass was prepared and studied during the sintering process. The illitic clay, from the Liepa deposit (Latvia), and green glass waste (GW) were disintegrated to obtain a homogeneous mixture. The addition of disintegrated GW (5–15 wt% in the mixture) led to a reduction in the intensive sintering temperature, from 900 to 860 °C, due to a significant decrease in the glass viscosity. The addition of GW slightly decreased the intensities of the endo- and exothermic reactions in the temperature range from 20 to 1000 °C due to the reduced concentration of clay minerals. GW reduced the plasticity of the clay and reduced the risk of structural breakage. The increase in sintering temperature from 700 to 1000 °C decreased the apparent porosity and water uptake capacity of the ceramics from 35% and 22%, down to 24% and 13%, respectively. The apparent porosities of all the sintered mixtures showed a decrease of between 6% to 9% after the addition of GW with concentrations from 5 up to 15 wt% respectively, while the water uptake capacities decreased from between 4% and 10%. The addition of GW led to an increase in the apparent density of the ceramic materials, up to 2.2 g/cm3. Furthermore, the compressive strength increased by more than two times, reaching a highest value of 240 MPa after the sintering of the 15 wt% GW-containing mixture at 1000 °C.